2019
DOI: 10.1038/s41598-019-56617-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum circular RNAs act as blood-based biomarkers for hypertrophic obstructive cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is one of the most common hereditary heart diseases and is associated with a high risk of sudden cardiac death. HCM is characterized by pronounced hypertrophy of cardiomyocytes, fiber disarray and development of fibrosis and can be divided into a non-obstructive (HNCM) and obstructive form (HOCM) therefore requiring personalized therapeutic therapies. In the present study, we investigated the expression patterns of several circulating circular RNAs (circRNAs) as potential biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 31 publications
0
40
0
2
Order By: Relevance
“…A study using whole blood revealed that the hsa_circ_0037911 level was significantly increased in hypertensive patients in contrast to the control group ( Bao et al, 2018 ). Another study revealed reduced expression levels of circRNAs (DNAJC6, TMEM56 and MBOAT2) in the serum of patients with HCM ( Sonnenschein et al, 2019 ). All three circRNAs had high discrimination power between HCM patients and the control cohort.…”
Section: Circrnas As Biomarkers For Cvdmentioning
confidence: 99%
See 2 more Smart Citations
“…A study using whole blood revealed that the hsa_circ_0037911 level was significantly increased in hypertensive patients in contrast to the control group ( Bao et al, 2018 ). Another study revealed reduced expression levels of circRNAs (DNAJC6, TMEM56 and MBOAT2) in the serum of patients with HCM ( Sonnenschein et al, 2019 ). All three circRNAs had high discrimination power between HCM patients and the control cohort.…”
Section: Circrnas As Biomarkers For Cvdmentioning
confidence: 99%
“…With the use of advanced technologies in sequencing and data analysis, a lot of circRNAs have been detected in human hearts and been reported to be associated with CVD ( Jakobi et al, 2016 ; Werfel et al, 2016 ; Fan et al, 2017 ; Tan et al, 2017 ) ( Table 2 and Figure 2 ). Moreover, circRNAs have been observed to have great potential as biomarkers for the diagnosis and prognosis of CVD ( Vausort et al, 2016 ; Sonnenschein et al, 2019 ; Wu et al, 2019 ; Vilades et al, 2020 ) ( Table 3 and Figure 2 ).…”
Section: Circrnas and Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the investigated circRNAs, DNAJC6, TMEM56, and MBOAT2 were found in serum and can help distinguish healthy from HCM patients. Furthermore, DNAJC6 and TMEM56 could serve as indicators for disease severity in patients with obstructive HCM (Sonnenschein et al, 2019). Identifying differentially regulated circRNAs through newly available sequencing technologies is the first step in planning further research with circRNAs.…”
Section: Circrnas In Cvdmentioning
confidence: 99%
“…Notably, Sry circRNA, previously reported to be predominant over linear Sry transcript in mouse testis (Capel et al, 1993), was not found. Significant new findings were the identification of several porcine heart-specific circRNAs related to hypertrophic cardiomyopathy, recapitulating circRNAs in human heart development and pathogenesis of cardiac diseases (Sonnenschein et al, 2019). Results identified MREs in 30% of the porcine circRNAs, implicating functionalities beyond miR sponging for porcine circRNAs.…”
Section: Swinementioning
confidence: 99%